Effects of Interleukin-1 Receptor Antagonist Overexpression on Infection by Listeria monocytogenes - Irikura, Vera M. (American Society for Microbiology, 1999)
Interleukin-1 receptor antagonist (IL-1ra) is a naturally occurring cytokine whose only known function is the inhibition of interleukin-1 (IL-1). Using a reverse genetic approach in mice, we previously showed that increasing IL-1ra gene dosage leads to reduced survival of a primary listerial infection. In this study, we characterize further the role of endogenously produced IL-1ra and, by inference, IL-1 in murine listeriosis. IL-1ra overexpression inhibits, but does not eliminate, primary immune responses, reducing survival and increasing bacterial loads in the target organs. We demonstrate that IL-1ra functions in the innate immune response to regulate the peak leukocyte levels in the blood, the accumulation of leukocytes at sites of infection, and the activation of macrophages during a primary infection. Reduced macrophage class II major histocompatibility complex expression was observed despite increased gamma interferon (IFN-γ) levels, suggesting that IL-1 activity is essential along with IFN-γ for macrophage activation in vivo. We also show that IL-1ra plays a more limited role during secondary listeriosis, blunting the strength of the delayed-type hypersensitivity response to listerial antigen while not significantly altering cellular immunity to a second infectious challenge. When these results are compared to those for other mutant mice, IL-1ra appears to be unique among the cytokines studied to date in its regulation of leukocyte migration during primary listeriosis.